Non-technical skills and teamwork in trauma: from the emergency department to the operating room - Alexandrino, Henrique; Martinho, Bárbara; Ferreira, Luís; Baptista, Sérgio (Frontiers in Medicine, 2023)
Management of a trauma patient is a challenging process. Swift and accurate clinical assessment is required and time-sensitive decisions and life-saving procedures must be performed in an unstable patient. This requires a coordinated response by both the emergency room (ER) and operating room (OR) teams. However, a team of experts does not necessarily make an expert team. Root cause analysis of adverse events in surgery has shown that failures in coordination, planning, task management and particularly communication are the main causes for medical errors. While most research is focused on the ER trauma team, the trauma OR team also deserves attention. In fact, OR team dynamics may resemble more the ER team than the elective OR team. ER and OR trauma teams assemble on short notice, and their members, who are from different specialties and backgrounds, may not train regularly together or even know each other beforehand. And yet, they have to perform high-risk procedures and make high stake decisions, in a time-sensitive manner. The airline industry has long recognized the role of team training and non-technical skills (NTS) in reducing hazards. The implementation of the so called crew resource management or crisis resource management (CRM) has significantly made airline travel safer and the transposition to the medical context, with specific training in non-technical skills, has also brought great benefits. In fact, it is clear that adoption of non-technical skills (NTS) in healthcare has led to an increase in patient safety. In this narrative review we recapitulate some of the key non-technical skills and their relevance in trauma, with a focus on both the emergency department (ER) and the operating room (OR) teams, as well as on the transition of care from one to the other. Also, we explore the use of debriefing the team, as well as the roles of NTS training in both undergraduate and postgraduate settings. We review some of the existing trauma training courses and their roles in developing NTS. Finally, we briefly address the challenges posed by the development of trauma hybrid operating rooms.